SISTEM INFORMASI PEMINJAMAN PADA POTMEETSHOP DENIM - Yohannes Yahya; T W Wisjhnuadji; Noviar Listianto (SYNTAX Jurnal Informatika)
ABSTRACTÂ The continued development of information technology is currently in need and the accuracy of the information thus facilitate the decision making. Information is needed to be useful for those who need the information so that whenever in need can be quickly accepted.At this time Potmeetshop Denim is still using the manual system, therefore Potmeetshop Denim employees often encounter problems such as the increasing complexity and constraints Potmeetshop Denim loan data, and transactions which resulted in frequent delays in service on the guest Potmeetshop Denim and report generation.With this system may result in ease of guest data, the data apparel, clothing loan data, the data of return clothing to the reports required by the employee Potmeetshop Denim and leadership, so that growth and development in terms of the circulation process will take place with the borrowing clothes fast and mainly will be implications with guest satisfaction in terms of lending Potmeetshop Denim clothing.Â Keywords : Potmeetshop Denim, clothes, information